Differences in the frequencies of HLA-class I and II alleles between German patients with renal cell carcinoma and healthy controls - Goebel, Steffen; Kehlen, Astrid; Bluemke, Karen; Altermann, Wolfgang; Schlaf, Gerald; Fischer, Kersten; Fornara, Paolo; Wullich, Bernd; Wach, Sven; Taubert, Helge (Cancer Immunology, Immunotherapy, 2017)
The human leukocyte antigen (HLA) system is a major part of the human immune system and has an impact on tumor initiation, tumor progression, and immunosurveillance. Renal cell carcinoma tumors are considered to be immunogenic. Therefore, we studied the allele frequencies of four gene loci (HLA-A, -B, -C, and HLA-DR) in a cohort of German renal cell carcinoma (RCC) patients and in healthy controls. HLA-A-C were determined using serological methods, whereas HLA-C12, C14, C16, C18, and HLA-DR were characterized through the use of standard molecular biological methods. The occurrence of the HLA-C*12 allele was significantly increased in German RCC patients compared with healthy controls (P < 0.005; Fisher's exact test), whereas the occurrence of the HLA-DRB1*04 allele was significantly reduced in RCC patients compared with healthy controls (P < 0.05; Fisher's exact test). However, the presence of allele HLA-C*12 was not significantly associated with 10 year overall survival. We suggest that the frequency of HLA alleles can affect development of RCC and could add knowledge as predictive marker for future immunotherapies.
EVALuna:33572